2007
DOI: 10.1211/jpp.59.10.0001
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical applications for catanionic mixtures

Abstract: Mixtures of oppositely charged surfactants, so called catanionic mixtures, are a growing area of research. These mixtures have been shown to form several different types of surfactant aggregates, such as micelles of various forms and sizes, and lamellar structures, such as vesicles. In this review, a short introduction to the field of catanionic mixtures is presented and the pharmaceutical possibilities offered by such mixtures are reviewed. There are several interesting ideas on how to apply catanionic mixtur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
87
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(91 citation statements)
references
References 107 publications
0
87
0
3
Order By: Relevance
“…The potential use of surfactants in pharmaceutical and biological applications 1,2,3,4,5,6 makes the evaluation of cytotoxicity and environmental behaviour of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…The potential use of surfactants in pharmaceutical and biological applications 1,2,3,4,5,6 makes the evaluation of cytotoxicity and environmental behaviour of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this shortcoming, various approaches have been employed to adjust the inter-vesicle and/or intra-vesicle interactions and thereby enhance the catanionic vesicles physical stability. Bramer et al 6 reviewed several catanionic vesicle studies investigating the use of multiplechained IPAs 9, 13 , bolaamphiphiles and dimeric or gemini surfactants 10,11 , and polymerized IPAs 55,56 , which could improve the membrane tightness of the vesicular structures. Recently, Marques and co-workers reported that IPAs containing cationic and anionic moieties with highly mismatched solubilities displayed remarkable phase behavior in water 59 63 .…”
Section: Ipasmentioning
confidence: 99%
“…Mixtures of oppositely charged surfactants can be classified into two types: catanionic mixtures or catanionic surfactants and ion pair amphiphiles IPAs . The former include counterions, whereas in the latter, the counterions are removed, leaving the two oppositely charged amphiphilic ions 4,6 . In early studies, the phase behavior of catanionic mixtures indicated that the vesicle domains exist in the excess cationic or anionic surfactant region and the low-concentration region, whereas precipitation generally occurs under equimolar conditions 4,5,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Cationic surfactants with this architecture exhibit a much higher surface activity than their monomeric counterparts, can easily be adsorbed at interfaces, and can interact with the cellular membranes of microorganisms, giving them high antimicrobial activity. Owing to their special ability to selfassemble, they show great promise in various areas, such as gene transfection [8][9][10][11], drug entrapment and release [12][13][14], and vitamin solubilization [15], and as components of body care products [16] and antibacterial and antifungal formulations [17,18]. Conventional cationic surfactants are highly chemically stable, but have poor chemical and biological degradability, which limits their use.…”
Section: Introductionmentioning
confidence: 99%